APPLICATIONS OF NANOTECHNOLOGY WITH HYBRID PHOTOVOLTAIC/THERMAL SYSTEMS: A REVIEW - Alktranee, Mohammed; Bencs, Peter (Journal of Applied Engineering Science, 2020)
This paper appears potential of use nanofluids as a working fluid with the photovoltaic/thermal (PV/T) systems as an alternative of the conventional liquids in improves the efficiency of the hybrid PV/T system. The review highlights the impact of some parameters (base fluid, volume fraction, the concentration of nanoparticles, surfactants, shape, and size of nanoparticles) on nanofluids’ thermophysical properties and their effect on the PV/T system’s efficiencies. Hence, it discusses the PV/T behavior, which uses different nanofluids based on previous experimental, analytical, and numerical studies. The review concluded that using nanofluid as a cooling fluid or spectral filter contributes by enhancing the performance and increasing the PV/T system’s efficiency. Thus, each type of nanofluids has certain features that contribute to removing the PV cells’ excess heat by cooling it, contributing to its work’s stability, and increasing its productivity. Nanofluids thermophysical properties play an intrinsic role by enhancing nanofluids’ performance, thus positively reflecting on the PV/T system’s performance. Despite the variation in the values of thermal and electrical efficiency, Most of the studies that used nanofluids have achieved encouraging results that appeared by improving the performance of PV/T systems.